Impact of Computer on Human Health (Journal of the College of Education for Women, 2019)
As computers become part of our everyday life, more and more people are experiencing avariety of ocular symptoms related to computer use. These include eyestrain, tired eyes, irritation,redness, blurred vision, and double vision, collectively referred to as computer vision syndrome.The effect of CVS to the body such as back and shoulder pain, wrist problem and neck pain.Many risk factors are identified in this paper.Primary prevention strategies have largely been confined to addressing environmentalexposure to ergonomic risk factors, since to date, no clear cause for this work-related neck painhas been acknowledged. Today, millions of children use computers on a daily basis. Extensiveviewing of the computer screen can lead to eye discomfort, fatigue, blurred vision and headaches,dry eyes and other symptoms of eyestrain. These symptoms may be caused by poor lighting,glare, an improper work station set-up, vision problems of which the person was not previouslyaware, or a combination of these factors. Children can experience many of the same symptomsrelated to computer use as adults. However, some unique aspects of how children use computersmay make them more susceptible than adults to the development of these problems.In this research we took the adult and children as a case study, questioner are made to rich thisresearch and finally some preventions are listed to immune from the impact of computer..